The Personal Values Practiced by the Students of English Language Teaching Methods at Hebron University from their Point of View - أبو منشار, منال (مجلة العلوم التربوية والنفسية, 2023)
This study aimed to reveal the personal values practiced by the students of English teaching Methods at the University of Hebron from their point of view. To achieve this goal, a questionnaire consisting of 40 statements has been built. The study was applied to a random sample based on (120) Students during the first semester of the academic year 2020-2021 (n=250). The results of the study showed that the degree of students' practice in the fields of values as a whole was high. The data indicate that social values got the highest estimate. Second, the economic values followed by the religious values. Fourth, aesthetic values. Fifth, the political values and last the cognitive values. The presence of statistically significant differences is attributed to the academic level variable in favor of the fourth-year students. In light of these results, the study recommended the development and enhancement of personal values on an ongoing basis, and the preservation and deepening of the value system of students at all academic levels.